Beyond the sovereign self aesthetic autonomy from the avant-garde to socially engaged art - Kester, Grant H. 1959- (Duke University Press, 2024)
"In Beyond the Sovereign Self Grant H. Kester continues the critique of aesthetic autonomy begun in The Sovereign Self, showing how socially engaged art provides an alternative aesthetic with greater possibilities for critical practice. Instead of grounding art in its distance from the social, Kester shows how socially engaged art, developed in conjunction with forms of social or political resistance, encourages the creative capacity required for collective political transformation. Among others, Kester analyzes the work of conceptual artist Adrian Piper, experimental practices associated with the escrache tradition in Argentina, and indigenous Canadian artists such as Nadia Myer and Michèle Taïna Audette, showing how socially engaged art catalyzes forms of resistance that operate beyond the institutional art world. From the Americas and Europe to Iran and South Africa, Kester presents a historical genealogy of recent engaged art practices rooted in a deep history of cultural production, beginning with nineteenth-century political struggles and continuing into contemporary anticolonial resistance and other social movements"--
Includes bibliographical references and index
Keywords: Engagierte Kunst; Ästhetik; Art / Philosophy; Art criticism; Autonomy (Psychology) in art; Subjectivity in art; Avant-garde (Aesthetics) / History / 20th century; Art, Modern / Political aspects; Art and society / History / 20th century; ART / Criticism & Theory; PHILOSOPHY / Aesthetics